Meningkatkan Kemampuan Penalaran Dan KomunikasiMatematis Dengan Menggunakan Model Problem Based Learning (PBL) - Lisa Mawarni; Hidayat Hidayat (LPPM UMN Al Washliyah, 2023)
This research is a Classroom Action Research which aims to improve mathematical reasoning and communication skills using the Problem Based Learning (PBL) model. The subjects in this study were all students of class VIII-1 MTs. TPI Medan, totaling 30 students. This research was conducted in 3 cycles, namely the first cycle consisting of 2 meetings, the second cycle 2 meetings and the third cycle 2 meetings. The instruments used in this study were observation guidelines, cycle tests, student response questionnaires, interview guidelines and documentation. The results showed that the students' mathematical reasoning and communication skills in class VIII-1 MTs. TPI Medan experienced an increase from cycle I, cycle II and cycle III. This was shown by 29 students or 96.66% experiencing an increase in mathematical reasoning and communication skills based on the total score of aspects of mathematical reasoning and communication skills. The average percentage of test scores increased from 46.58% in cycle I to 55.86% in cycle II and to 83.14% in cycle III in the high category. Based on the results of observations of the implementation of learning with the PBL model, it is good and in accordance with the characteristics of PBL. This is indicated by an increase in the average percentage of implementation from 85.71% in cycle I to 92.86% in cycle II and to 100% in cycle III. Based on the results of the interviews and data from the questionnaire results of students' responses to learning mathematics in relation to mathematical reasoning and communication abilities, there was an increase from cycle I, cycle II and cycle III. Thus, students have a positive response to learning mathematics with the PBL model as an effort to improve mathematical reasoning and communication skills.